Designing customer experience on the example of a steam screening service - Zielińska-Chmielewska, Anna; Mruk-Tomczak, Dobrosława; Stelmach , Katarzyna (Management and Administration Journal, 2025)
The article is devoted to the process of designing the customer experience using the example of an innovative service, which is a steam session conducted by a sauna master in a dry sauna. The aim of the article is to analyze and evaluate the attractiveness of the determinants of the experience of the steam seance service and to provide recommendations for service providers on the design of this type of service. The study used primary data in the form of a survey questionnaire conducted among steam seance customers and secondary data in the form of a literature review. The presented results of the own research were enriched with conclusions from research in the field of customer experience design, as well as a thorough analysis of diverse literature. On this basis, conclusions, recommendations for service providers and service recipients were presented along with limitations of the research and future research directions to optimally match the growing expectations of consumers of the developing health and well-being sector in Poland.